A Good Result for Blowfish Image Encryption Based on Stepic - Cahyani, Anis Putma; Susanto, Ajib (Universitas PGRI Semarang, 2024)
Information security is important in the era of evolving communications. Security methods are needed to protect data. Strong cryptographic algorithms, such as Blowfish, developed by Bruce Schneier in 1993, offer fast and reliable encryption. Blowfish uses 64 bit blocks and key lengths between 32 and 443 bits. This algorithm is famous for its robustness and encryption speed, with a Feistel Network structure and 16 rounds. This research implements Blowfish with Python and integrates it with steganography to insert secret data in digital images. Evaluation involves metrics such as Mean Squared Error (MSE), Peak-Signal-to-Noise Ratio (PSNR), Average Visibility (AVA), Uniform Average Change Intensity (UACI), and Percentage Pixel Change Value (NPCR) to measure quality and reliability encryption and decryption process by Blowfish.